2019
DOI: 10.1017/ipm.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic burden of patients with dementia attending a Psychiatry of Later Life service

Abstract: Objectives. Older adults with dementia are particularly vulnerable to adverse outcomes resulting from anticholinergic use. We aimed to: (i) Examine the anticholinergic burden of patients with dementia attending a Psychiatry of Later Life (PLL) service (ii) Examine concomitant prescription of acetylcholinesterase inhibitors (AChEIs) and anticholinergics and (iii) Compare the Anticholinergic Cognitive Burden (ACB) scale with a recently published composite list of anticholinergics. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a study of 341 community-dwelling elderly in the USA, West et al reported that persons who had total ACB scores greater or equal to 3 made up 47.8% of the cohort [ 21 ], while Cebron Lipovec et al in 2020 reported that this same subset constituted 12.1% of their cohort [ 20 ]. Vaughan et al reported that 37.9% of hospitalized patients with dementia had ACB ≥ 3 or were prescribed one medication with an ACB of 2 or higher [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 341 community-dwelling elderly in the USA, West et al reported that persons who had total ACB scores greater or equal to 3 made up 47.8% of the cohort [ 21 ], while Cebron Lipovec et al in 2020 reported that this same subset constituted 12.1% of their cohort [ 20 ]. Vaughan et al reported that 37.9% of hospitalized patients with dementia had ACB ≥ 3 or were prescribed one medication with an ACB of 2 or higher [ 22 ].…”
Section: Discussionmentioning
confidence: 99%